2022
DOI: 10.1186/s12889-022-14343-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a locally tailored intervention on the uptake of preconception care in the Netherlands: a stepped-wedge cluster randomized trial (APROPOS-II study)

Abstract: Background The preconception period provides a window of opportunity for interventions aiming to reduce unhealthy lifestyle behaviours and their negative effect on pregnancy outcomes. This study aimed to assess the effectiveness of a locally tailored preconception care (PCC) intervention in a hybrid-II effectiveness implementation design. Methods A stepped-wedge cluster randomized controlled trial was performed in four Dutch municipalities. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 64 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…Nine of the included studies were RCTs, [30][31][32][33][34][35][36][37] and one was a cohort study adopting a pre-post-test analysis. 38 Publication ranged from July 2010 to November 2022 with five studies undertaken in the Netherlands, 30,31,35,37,39 three in the United States of America (USA) 32,36,38 and one each from Australia 34 and Malaysia. 33 The study populations consisted of non-pregnant women aged between 18 and 44 years.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine of the included studies were RCTs, [30][31][32][33][34][35][36][37] and one was a cohort study adopting a pre-post-test analysis. 38 Publication ranged from July 2010 to November 2022 with five studies undertaken in the Netherlands, 30,31,35,37,39 three in the United States of America (USA) 32,36,38 and one each from Australia 34 and Malaysia. 33 The study populations consisted of non-pregnant women aged between 18 and 44 years.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies also reported on behaviours in men, which was outside the scope of this review. 35,37,39 Four studies specifically included women who had an overweight or obese BMI, 30,31,34,38 the rest did not specify a BMI range. One study included women with polycystic ovary syndrome.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations